THE DIFFERENCES BETWEEN TEACHING ADULT AND CHILDREN - Tolibpva, Shokhzoda (Журнал иностранных языков и лингвистики, 2021)
One of the first things to remember about kids is that their brains have more elasticity than those of adults. Their brains are not “formed” yet, so to speak. As a result, it is easier for children to learn a new language. As people become older, taking on a new language becomes a lot more difficult than learning it in early ages.